Stakeholder engagement in the pooled procurement program in Ghana - Domfeh, K. A.; Appiah-Agyekum, N. N. (Oxford University Press, 2023)
Objective: The article explores stakeholders’ engagement before the implementation of the pooled procurement program (PPP) and the challenges encountered by the National Catholic Health Service (NCHS). Method: The article used a qualitative research approach and a multiple case study design to solicit the views of healthcare service providers and policymakers within the NCHS. Key findings: The article revealed that the National Catholic Health Secretariat (the secretariat) advocated through the Ghana Catholic Bishops Conference through the bishop responsible for health. Subsequently, the Diocesan Directors, managers, accountants, suppliers and storekeepers of all health facilities were engaged to understand their respective roles before implementing the PPP. The challenges faced came from all institutions that played a crucial role in the smooth running of the PPP. These institutions were the hospitals, suppliers, Food and Drugs Authority (FDA), National Health Insurance Scheme (NHIS) and the secretariat. The findings indicated that some managers in the hospitals were not committed to the program. Whereas, some suppliers purposely weakened the position of some other suppliers after awarding tenders by carrying their commodities directly to the hospitals and reducing the price marginally. The challenge from the NHIS perspective was the payment delays. The FDA was not proactive with post-market surveillance to check substandard commodities in the hospitals. However, in the secretariat, the deficiency was the weak systems to monitor real-time activities of the PPP at the hospitals. Conclusion: The article suggests that to ensure the right synergies to meet organizational objectives, the NCHS is advised to increasingly focus on identifying and sustaining the PPP by communicating with other stakeholders to achieve their mutual needs. Such a process would allow the more knowledgeable design of resource needs and allocation of scarce resources to their areas of interest
Research Article
Keywords: Stakeholder engagement; Pooled procurement program; Ghana